Developmental Trajectories of Maternal Sensitivity across the First Year of Life: Relations among Emotion Competence and Dyadic Reciprocity - van Huisstede, Lauren (Parent Sci Pract, 2019)
OBJECTIVE. Maternal sensitivity is a commonly used construct to capture the quality of mother-child interactions, but inconsistencies in conceptualizing and defining maternal sensitivity limit understanding of how sensitive caregiving may be associated with child development. The purposes of this study are to (1) examine and compare the developmental trajectories of individual maternal sensitivity behaviors to that of a global index of sensitivity across the first year of infant life and (2) determine whether differences in trajectories of sensitivity are meaningful for infant emotion competence and dyadic reciprocity at 12 months. DESIGN. A total of 322 low-income, Mexican American mothers and infants were observed during a free play task at 3, 4.5, 6, and 12 months. Observations were coded for 11 distinct behaviors known to compose maternal sensitivity. At 12 months, mother-infant interactions were also coded for dyadic reciprocity, and mothers reported on infant emotion competence. RESULTS. Latent growth models indicated that individual sensitivity behaviors differed from the global index of sensitivity with respect to initial levels and slopes, with increasing (e.g., vocal appropriateness), decreasing (e.g., touch), and stable (e.g., elaboration) trajectories. The individual and global indices of sensitivity differed in prediction of emotion competence and dyadic reciprocity. Trajectories of global and individual indices of maternal sensitivity operated similarly in predicting dyadic reciprocity, with the exception of consistency of style. In contrast, the global index of sensitivity was unrelated to emotion competence, and only initial levels of positive affect emerged as significant predictors of emotion competence. CONCLUSIONS. The findings offer a more nuanced understanding of maternal sensitivity and suggest that component aspects of maternal sensitivity uniquely contribute to child and family competencies.